GOLD MINERAL POTENTIAL MAPPING USING GEOGRAPHIC INFORMATION SYSTEMS (GIS) IN THE LAO PDR - , Onexayvieng, Phetviengkham ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Spatial data integration and analysis for predicting gold mineral potential are carried out on the available comparation. In the search for gold mineral potential areas, accurate and make gold potential maps that are essential as it represents the most basic information for directing exploration activities. Gold mineral potential map is necessary for mineral exploration operate especially mapping of the mineral potential in the probability area. The study area is in Lao PDR. It is covered 235,071 km2 consisting of all provinces. It is interesting areas for exploration of metallic mineral deposits, especially the gold deposits occurrences are associated with lithology unit age Permain and Triassic, such as porphyry and epithermal deposits. Mineral exploration is multi stage activity that begins at a small scale and progress to a large scale. That is associated with increasing geosciences data. Geological information is important to determine which areas are favourable for the occurrence of particular types of mineralisation. Mineral resource information is important to determine, among others, the location of potentially-mineralized areas. GIS has greatly improved the possibilities for spatial data processing, analysis and visualization of geosciences data. The weight of evidence method and Bayesian method are used to combine and to calculate dataset using a probability framework. These methods are applied for mineral potential mapping through producing a new map showing posterior probability of study areas. The probabilistic mineral potential map are predict correctly 187 points (about 62%) of the known training deposits (272 points) by the geologic structures and host rocks condition covers 70,028 km2 and predicts correctly 75 (or about 83 %) of gold mineral deposits which are predict for verification.The probabilisitic areas are about 70,028 km2 (30% of total area of Lao PDR), which are gold mineral potential area for gold mineralization in Lao PDR. Key words: Gold mineral potential, geographic information systems, Lao PDR